Avaliação das taxas de vacinação e internação hospitalar por doença respiratória aguda em idosos - Boscato, Ana Paula (2018)
Introduction Global populational aging is a current reality and a concern for the future. The raise of infection vulnerability makes the elderly an important target population for vaccination. Knowledge of the population over 60 and / or their caregivers about immunoprevention is unknown in Brazil. Objectives To analyze the rate of anti-pneumococcal vaccination VPC13 and VPP23, against influenza, in addition to studying the frequency of hospital admission for acute respiratory disease in individuals over 60 years of age. It was also intended to evaluate the vaccination rates for herpes zoster, hepatitis B and diphtheria-tetanus-pertussis acellular (dTpa) and verify the knowledge of the patients, their relatives or caregivers about the vaccination schedule. Design Cross-sectional epidemiological study, of the elderly attended at the Geriatric Outpatient Clinic of Military Hospital of Porto Alegre, Brazil between October 31, 2016 and June 1, 2017. The size of the sample at 128 was based on the significance level of 95%, vaccination rates between 15 and 80%, prediction of 720 visits in 6 months, and margin of error of 7%. Patients and relatives or caregivers were submitted to the standardized questionnaire, after signing the consent form. Pearson's t-student test, Fischer's exact chi-square test was used to analyze data, and the multivariate analysis of Poisson regression was used to assess the factors associated with hospitalization for respiratory disease. Results Sample composed of 129 participants. None of them had a thoroughly filled vaccination calendar. The hospitalization rate by respiratory disease in the last year was 11,6%. There was no statistically significant difference in the frequency of hospital admission in individuals who did or did not take vaccines against respiratory diseases. Elderly patients with chronic obstructive pulmonary disease (COPD) proportionally hospitalized more when compared to elderly without COPD (p = 0,02). Conclusion The elderly in this sample are not completely immunoprevented and a small percentage (n=12; 9,3%) had not received any vaccination. There was no statistically significant difference between taking influenza vaccines, VPC 13 or VPP 23 and hospitalization for respiratory disease.